"Snake" instability of charge compensated nonuniform electron beam - Vladimir Petrovich Grigoriev; I. L. Zvigintsev; P. E. Kuznetsov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2009)
The large-scale lateral instability of charge partially compensated electron beam conditioned by resonance of coupled transverse oscillations of electron flow and ion channel is studied. The instability increments have been determined depending on wave length. It was shown that the instability is controlled on nonlinear stage due to lateral perturbation strength dependence on beam shift from equilibrium path.